L’istituto Sperimentale di Rete Ferroviaria Italiana - Terrinoni, Rodolfo (GEOmedia, 2010)
Research Institute of Italian Rail Network After the establishment of the State Railways in 1905, Eng. Riccardo Bianchi, the first Director General, felt the need to establish the Research Institute, to give the new administration will train the scientific and technical means of testing and control of materials, the Research Institute, which was based on the impressive and prestigious building of the old station of Roma Trastevere, had immediately set up to conduct studies, research and experiments to define the characteristics and technical requirements of materials for the construction and operation of rail and to develop processes on the purchase order and delivery.